Meningkatkan Hasil Belajar Matematika Siswa SMP Negeri 3 Halmahera Selatan Melalui Penerapan Model Kooperatif STAD - Ade, Jufri (Peneliti.net, 2023)
This research aims to explore the application of the STAD cooperative learning model in Mathematics instruction to enhance learning achievement for eighth-grade students at SMP Negeri 3 Halmahera Selatan. The method applied in this research is Classroom Action Research (CAR) through two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this research are 25 eighth-grade students at SMP Negeri 3 Halmahera Selatan. The research findings indicate that the use of the STAD cooperative learning model in Mathematics instruction successfully improves the learning achievement of eighth-grade students at SMP Negeri 3 Halmahera Selatan. This is evident from the increase in students' post-test scores in each learning cycle. In the pre-cycle stage, only 44% of students reached the classical minimum completeness criteria (KKM) with an average score of 63.2. In Cycle I, the classical achievement increased to 72% with an average score of 75.4. Meanwhile, in Cycle II, the classical achievement increased to 92% with an average score of 82.6.